ROLAND BARTHES' SEMIOTIC ANALYSIS OF THE SYMBOLIC MEANING OF SUSTAINABILITY ON THE COVER OF PT PERTAMINA'S 2023 SUSTAINABILITY REPORT - A.Anggi Reskiamalia; Muh Silmi Kaffa Yusuf; Darwis; Alimuddin (RADJA PUBLIKA, 2026)
This study aims to analyze the symbolic meaning of sustainability contained in the cover of PT Pertamina's 2023 Sustainability Report using Roland Barthes' semiotic analysis. This approach is used to interpret the three layers of meaning: denotation, connotation, and myth that shape the company's sustainability image and ideology. This study uses a descriptive qualitative method with a focus on visual and narrative signs that represent sustainability messages. The analysis focuses on visual elements such as color, images, typography, and communication themes used on the report cover to build an image of social and environmental responsibility. In addition, this study also links the findings with legitimacy theory to explain how these visual representations function as a corporate communication strategy in gaining and maintaining social legitimacy. The results show that symbols such as blue and green, wind turbines, solar panels, and the theme